Analisis Berita Acara Pemeriksaan (BAP) dalam Kasus Tindak Pidana Pelecehan Seksual di Muka Umum (Pasal 281 KUHP) - Samara, Finsensius; Moata, Shelomita F; Muly, Melyn Christy R.K; Pulupina, Julisandri T.A; Riwu, Rosyani Harseni; Pule, Marnof Lebe; Atulolon, Boneventura Sawu (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This analysis aims to examine the formal and material completeness of the Minutes of Investigation (Berita Acara Pemeriksaan/BAP) and to analyze the fulfillment of the elements of a criminal offense in a case of public sexual harassment charged under Article 281 of the Indonesian Criminal Code (KUHP). The BAP under analysis involves the Suspect, Ariz Utama, and the Victim, Ardiana Rasnawati, and includes the entire process from investigation through trial proceedings before the South Jakarta District Court. Using a normative legal research method and document analysis, this study evaluates the conformity of the investigative process with the Indonesian Criminal Procedure Code (KUHAP), analyzes the fulfillment of the elements stipulated in Article 281 of the KUHP, and assesses the probative value of the evidence submitted. The results of the analysis indicate that the BAP satisfies both formal and material requirements, and that the collected evidence—particularly the suspect’s confession and the consistent testimony of the victim—is sufficiently strong to prove the criminal offense. Therefore, this case is appropriate and has met the requirements to proceed to the prosecution stage and judicial examination at trial. This analysis also includes an alternative decision (obiter dictum) based on legal considerations prior to the pronouncement of the judge’s verdict.